Building Cognitive and Affective Learning Outcomes on the Concept of Linear Motion through Ticker Timer Experiment Using Problem Based Learning - Khoiri, Nur; Huda, Choirul; Wiyanto, Wiyanto (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2020)
This study is aimed to determine the impact of the ticker timer experiment using Problem Based Learning (PBL) model on students’ cognitive and affective learning outcomes in Physics. The research used a quasi-experimental method which is conducted in one of the senior high schools in Semarang, Indonesia. The research subject for both experimental and control classes was chosen randomly from the population. The experimental class carried out the learning using the PBL model-based experiment and the control class implemented the Direct Instruction model. The cognitive and affective learning outcomes were collected through the test and the observation sheets. The data analysis used the t-test statistical method. The results showed that there were differences in cognitive learning outcomes between the control class and the experiment class (tcount = 1.993> ttable = 1.667). Based on the results of the observations also found differences in students' affective learning outcomes with the average value of the experimental class was 25 which is in the very good category and 23.21 for the control class which is in the good category. Based on the results of the discussion, it can be concluded that the PBL model-based experiment has a significant impact on students' cognitive and affective learning outcomes